Prognostic value of PD-1, PD-L1 and PD-L2 deserves attention in head and neck cancer - Jiang, Siqing; Li, Xin; Huang, Lihua; Xu, Zhensheng; Lin, Jinguan (Frontiers in Immunology, 2022)
Head and neck cancer has high heterogeneity with poor prognosis, and research on the prognostic markers of head and neck cancer emerges one after another. PD-L1 expression is an important reference for strategies of immunosuppressive treatment, but whether it has prognostic value is still controversial. Even if a meta-analysis of PD-L1 expression versus head and neck cancer prognosis is conducted, the conclusions are still controversial. There are PD-L1 and PD-L2 as receptors for PD-1. We summarize the different prognostic values of PD-1, PD-L1, and PD-L2 in head and neck cancer at different stages of disease development, different cell types, tissue localization, and protein forms. We propose that in the context of head and neck cancer, the risk warning value of PD-1/PD-L1 expression in precancerous lesions should be paid attention to, and the prognostic value of PD-L1 expression at different subcellular levels should be discussed, and the convenience of judgment of prognostic value of PD-1,PD-L1,PD-L2 should be fully considered. The PD-L1 evaluation systems established based on immune checkpoint inhibitors (ICIs) are not fully suitable for the evaluation of PD-L1 prognosis in head and neck cancer. It is necessary to establish a new PD-L1 evaluation system based on the prognosis and conduct related explorations. The prognostic value of PD-L1,PD-L2 expression in head and neck cancer may be different in early-stage and late-stage samples, and further stratification is required.